The Impact of Meditation on Brain Structure Changes and Cognitive Function in Young Adults - Santos, Luis; Reyes, Maria Clara; Malik, Fatima; Iqbal, Kiran; Nampira, Ardi Azhar (World Psychology, 2025)
Meditation has gained significant attention for its potential to enhance cognitive function and promote mental well-being. Previous studies have suggested that meditation can lead to structural changes in the brain, particularly in regions associated with attention, memory, and emotional regulation. However, the precise impact of meditation on brain structure and cognitive function in young adults remains underexplored. This study aims to investigate the effect of regular meditation practice on brain structure changes and cognitive function in young adults. A mixed-methods approach was employed, including structural magnetic resonance imaging (MRI) to assess brain changes and cognitive function assessments, such as attention, memory, and executive function tests, conducted before and after a 12-week meditation intervention. The results showed significant increases in gray matter density in areas related to attention and emotional regulation, including the prefrontal cortex and hippocampus. Cognitive testing revealed improvements in attention, working memory, and cognitive flexibility. These findings suggest that meditation can induce structural changes in the brain that enhance cognitive function, particularly in domains critical for academic and personal development. The study concludes that meditation can be an effective practice for promoting cognitive health and supporting brain development in young adults, highlighting its potential as a non-invasive intervention for cognitive enhancement.